High-content imaging for automated determination of host-cell infection rate by the intracellular parasite Trypanosoma cruzi - Nohara, L.L. (2010)
Chagas disease affects 8–11 million people, mostly in Latin America. Sequelae include cardiac, peripheral nervous and/or gastrointestinal disorders, thus placing a large economic and social burden on endemic countries. The pathogenesis and the evolutive pattern of the disease are not fully clarified. Moreover, available drugs are partially effective and toxic, and there is no vaccine. Therefore, there is an urgent need to speed up basic and translational research in the field. Here, we applied automated high-content imaging to generate multiparametric data on a cell-by-cell basis to precisely and quickly determine several parameters associated with in vitro infection of host-cell by Trypanosoma cruzi, the causative agent of Chagas disease. Automated and manual quantification was used to determine the percentage of T. cruzi-infected cells in a 96-well microplate format and the data generated was statistically evaluated. Most importantly, this automated approach can be widely applied for discovery of potential drugs as well as molecular pathway elucidation not only in T. cruzi but also other human intracellular pathogens.